ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA PT BANK OCBC NISP Tbk - Vargo Christian L. Tobing; Eva Malina Simatupang (Aktiva : Jurnal Akuntansi dan Investasi, 2022)
The title of research was an â€œAnalysis of Bank Health with RGEC Method at PT Bank OCBC NISPâ€. This research aimed to determine how the health of PT Bank OCBC NISP Tbk for the period 2019-2021. The population in this research was the financial statement of PT Bank OCBC NISP Tbk and the samples were the statement of Financial Position (balance sheet), Income Statement, and Notes to Financial Statement of PT Bank OCBC NISP Tbk for the 2019-2021 period. The type of data used in this research was secondary data obtained by documentation techniques throughÂ  PT Bank OCBC NISP Tbk website. The data analysis technique used was descriptive analysis using the RGEC method. Based on the results of the data analysis, it showed that PT Bank OCBC NISP TbkÂ  for the 2019-2021 period obtained the 1st composite rating (PK) or very healthy with a composite value of 93,33%. This reflects that PT Bank OCBC NISP Tbk is capable to deal with negative effects from business condition that may occur